2019
DOI: 10.1080/10962247.2019.1604451
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of tropospheric ozone at an industrial site of Chennai megacity

Abstract: This paper presents the temporal variation in surface-level ozone (O 3) measured at Gummidipoondi near Chennai, Tamilnadu. The site chosen for the present study has high potential for ozone generation sources, such as vehicular traffic and industrial activities. The site is also located near a hazardous waste management facility. The key sources of nitrogen oxides (NO x), which are considered to be an important precursor of O 3 , include hazardous waste incineration, trucks bringing the hazardous wastes, and v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 39 publications
1
13
0
Order By: Relevance
“…Pollutants except O3 are directly associated with traffic pollution. Tropospheric O3 is known as a secondary pollutant due to the increasing of ozone formation by other pollutants in the atmosphere (Mohan et al, 2019). Combustion of fossil fuels, vehicle exhausts and industry cause emission of NOX, CO, SO2 and VOCs as a primary air pollutant.…”
Section: Hourly Concentration Levels Of Pollutantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pollutants except O3 are directly associated with traffic pollution. Tropospheric O3 is known as a secondary pollutant due to the increasing of ozone formation by other pollutants in the atmosphere (Mohan et al, 2019). Combustion of fossil fuels, vehicle exhausts and industry cause emission of NOX, CO, SO2 and VOCs as a primary air pollutant.…”
Section: Hourly Concentration Levels Of Pollutantsmentioning
confidence: 99%
“…In the troposphere O3 is formed or its concentration increases at the end of photochemical reactions (Bozkurt et al, 2018). The concentration of NOX and intensity of solar radiation extremely affect the formation and concentration of O3 (US EPA 2020a; Bozkurt et al, 2018;Mohan et al, 2019). As a result, the highest levels of ozone pollution occur during periods of sunny weather (WHO, 2000).…”
Section: Hourly Concentration Levels Of Pollutantsmentioning
confidence: 99%
“…Other studies have also shown that the ozone concentration is significantly positively correlated with solar radiation intensity [59,60]; however, most studies have discussed the daily or seasonal variations of ozone concentration, and fewer studies have focused on the relationship between interannual ozone concentration and solar radiation.…”
Section: Solar Radiationmentioning
confidence: 99%
“…Its concentrations range between 0.05-0.22 ppb in the remote troposphere (Stratmann et al, 2016) and 0.5-73 ppm in the polluted troposphere (Mohan & Saranya, 2019). Because of the rapid development of agriculture, industry and mega-cities, anthropogenic activities have dramatically affected the release of NO into the atmosphere.…”
Section: Introductionmentioning
confidence: 99%